A Proposed Training Program for Developing Technology Integration Skills in Basic Education for Social Studies Teachers in Sana'a City in Light of Their Training Needs - Al-Emad, Nabil Abdullah Qaid; Al-Salahi, Abdussalam Mohammed Ahmed; Al-Faqeeh, Najat Hasan Hasan (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to build a proposed training program to develop technology integration skills for Social Studies teachers in Sana'a City in light of their training needs. To achieve the study's objective, the researcher used the descriptive survey method. The tool was a questionnaire applied to a random sample of (150) Social Studies teachers in Sana'a City. The study results revealed that the training needs obtained a total average of (2.00 out of (3) with a rating of (medium). The most needed skills were (interactive whiteboard use, with an average of (2.96), then designing electronic tests using Google Forms models (278), and thirdly utilizing the internet and creating e-mail (2.72), and fourthly presentation software (PowerPoint) (2.64), and fifthly Windows usage skills (2.62), all with a need rating of (high). Based on identifying the needs and then building a proposed training program to develop technology integration skills in Basic Education for Social Studies teachers in Sana'a City in light of their training needs, the program was also reviewed by many experts and specialists. The researcher recommended applying the program to social studies teachers.
Keywords: Technology integration; Basic Education; Social Studies teachers; training needs